Semiotic criteria for analyzing religious symbols in press reports Qantara news site as a model - Najm, Wedad (ALBAHITH ALALAMI, 2022)
The report includes a group of symbols that are employed within a framework that gives a language of greater impact. This research discusses the problem of the semiotic employment of religious symbols in press reports published in the electronic press across two levels: Reading to perceive the visual message in its abstract form, and the second for re-understanding and interpretation, as this level gives semantics to reveal the implicit level of media messages through a set of semiotic criteria on which it was based to cut texts to reach the process of understanding and interpretation.The report includes a group of symbols that are employed within a framework that gives a language of greater impact. This research discusses the problem of the semiotic employment of religious symbols in press reports published in the electronic press across two levels: Reading to perceive the visual message in its abstract form, and the second for re-understanding and interpretation, as this level gives semantics to reveal the implicit level of media messages through a set of semiotic criteria on which it was based to cut texts to reach the process of understanding and interpretation.The survey method followed the method of surveying with the intentional sample, and this research belongs to the type of descriptive research by the qualitative method. the vertical to delve deeper into reaching the major connotations, and a set of results were reached, namely: the deep and superficial structures dominated the religious and political spirit, and the structures came in introductory and not confrontational formulas It tends to instill a spirit of reassurance more than confrontation, but it was not devoid of the style of intimidation, intimidation and threat, as well as expressions of coexistence, dialogue, peace and finding common ground between religions. To violence, as it followed the mechanism of invoking the special effects of the case from the external environment through a persuasive message that leads to modifying and activating the awareness of the recipient to obtain absolute conviction.